Expanding the clinical phenotype in patients with disease causing variants associated with atypical Usher syndrome. (2nd November 2021) - Igelman, Austin D.; Ku, Cristy; da Palma, Mariana Matioli; Georgiou, Michalis; Schiff, Elena R.; Lam, Byron L.; Sankila, Eeva-Marja; Ahn, Jeeyun; Pyers, Lindsey; Vincent, Ajoy; Ferraz Sallum, Juliana Maria; Zein, Wadih M.; et al.
ABSTRACT: Atypical Usher syndrome (USH) is poorly defined with a broad clinical spectrum. Here, we characterize the clinical phenotype of disease caused by variants in CEP78, CEP250, ARSG, and ABHD12 . Chart review evaluating demographic, clinical, imaging, and genetic findings of 19 patients from 18 families with a clinical diagnosis of retinal disease and confirmed disease-causing variants in CEP78, CEP250, ARSG, or ABHD12 . CEP78 -related disease included sensorineural hearing loss (SNHL) in 6/7 patients and demonstrated a broad phenotypic spectrum including: vascular attenuation, pallor of the optic disc, intraretinal pigment, retinal pigment epithelium mottling, areas of mid-peripheral hypo-autofluorescence, outer retinal atrophy, mild pigmentary changes in the macula, foveal hypo-autofluorescence, and granularity of the ellipsoid zone. Nonsense and frameshift variants in CEP250 showed mild retinal disease with progressive, non-congenital SNHL. ARSG variants resulted in a characteristic pericentral pattern of hypo-autofluorescence with one patient reporting non-congenital SNHL. ABHD12 -related disease showed rod-cone dystrophy with macular involvement, early and severe decreased best corrected visual acuity, and non-congenital SNHL ranging from unreported to severe. This study serves to expand the clinical phenotypes of atypical USH. Given the variable findings, atypical USH should be considered in patients with peripheral and macular retinal disease even without the typical RP phenotype especially when SNHL is noted. Additionally, genetic screening may be useful in patients who have clinical symptoms and retinal findings even in the absence of known SNHL given the variability of atypical USH.